Soluble Human Leukocyte Antigen‐G in Seminal Plasma is Associated with HLA‐G Genotype: Possible Implications for Fertility Success. (16th April 2014) - Dahl, Mette; Perin, Trine L.; Djurisic, Snezana; Rasmussen, Merete; Ohlsson, Janni; Buus, Søren; Lindhard, Anette; Hviid, Thomas Vauvert F.
<x xml:space="preserve">Abstract</x> Problem We have previously shown that human seminal plasma contains immunomodulatory soluble HLA‐G (sHLA‐G). We investigated whether sHLA‐G levels in seminal plasma are associated with a specific 14 base pair (bp) insertion/deletion (ins/del) polymorphism in the 3′‐untranslated region of the HLA‐G gene and/or with the outcome of assisted reproduction treatments (ART) in couples attending a fertility clinic. Method of Study In a total of 54 unselected couples, sHLA‐G levels were measured in seminal plasma samples and blood samples, HLA‐G genotyping was performed, and clinical data were collected. Results The concentration of sHLA‐G in seminal plasma samples was significantly associated with the HLA‐G 14 bp ins/del genotype of the men; the del14 bp/del14 bp genotype showed the highest level of sHLA‐G, and the ins14 bp/ins14 bp genotype showed the lowest level (P = 0.003). We observed a trend for higher seminal plasma levels of sHLA–G/total protein and total sHLA‐G in cases with reduced semen quality, where the female partner became pregnant after ART, compared with those couples in which no pregnancy was achieved. Conclusion These first results are in accordance with a possible role of seminal sHLA‐G as an immunomodulatory factor in the female reproductive tract before and at the time of conception.